Orientation Towards Symmathesy and Organizational Markers as Means to Cultivate Art Talent Environments: An Empirical Study Researching the Emergence of Talent Environments for Young Artists - Nørlem, Jakob; Stegeager, Nikolaj (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2023)
This article presents a study on the development of art environments for young talented artists across 4 municipalities in the western part of Jutland, Denmark. Within this context and based on systems thinking, neosystems thinking and a holistic ecological approach to talent development, the researchers identify and describe three transcontextual art talent environments (Off-Track, Film, Show-up). Based on the neo-systemic concepts of symmathesy (Together-learning), the pivotal point in this study, was to identify organizational markers in the development of a strong talent infrastructure across the municipalities. This to enable and cultivate the artistic potential of young people.The research question of the study was: Which organizational markers cultivate the development of art talent environments in the context of four Danish municipalities in the western part of Jutland? The study is based on interviews with seven different public servants from different municipalities in the western part of Jutland and build on a prior research regarding young artists within different artistic fields and their instructors.Through a generic thematic analysis, four organizational markers were identified (organizing, strategizing, license to operate, and creative places). The paper argues that an orientation towards environments as a symmathesy and towards organizational markers can help organizations improve artistic talent environments across municipalities. Further, the role of public servants as talent stewards is discussed in the discussion.